Pengaruh Literasi Keuangan, Perilaku Keuangan, Efikasi Diri, dan Gender terhadap Minat Berinvestasi Gen Z - Agustinus Jaha Dili; Sari Rahmadhani (AKUA: Jurnal Akuntansi dan Keuangan, 2025)
This study aims to test and analyze the effect of financial literacy, financial behavior, self-efficacy, and gender on investment interest. Data were obtained through questionnaires administered to the Gen Z generation in the city of Semarang. Data analysis uses linear regression analysis. The results showed that financial literacy and financial behavior are the main drivers of interest in investing among Gen Z in Semarang, with a significant positive influence. This finding highlights the importance of strong financial education and the early development of frugal habits. In addition, the positive effect of gender suggests that investment education and promotion strategies could be more effective if customized, especially considering the higher interest of Gen Z women. Self-efficacy does not significantly affect investment intention, suggesting that barriers to investing may be more closely related to accessibility and ease of process than to self-confidence. To increase Gen Z Semarang's investment interest, the main focus should be on improving financial literacy and behavior, with a gender-sensitive approach, as well as simplifying the investment process.